2008
DOI: 10.1098/rspb.2008.0798
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid-based colour of acanthocephalan cystacanths plays no role in host manipulation

Abstract: Manipulation by parasites is a catchy concept that has been applied to a large range of phenotypic alterations brought about by parasites in their hosts. It has, for instance, been suggested that the carotenoid-based colour of acanthocephalan cystacanths is adaptive through increasing the conspicuousness of infected intermediate hosts and, hence, their vulnerability to appropriate final hosts such as fish predators. We revisited the evidence in favour of adaptive coloration of acanthocephalan parasites in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 59 publications
7
48
0
Order By: Relevance
“…Second, the benefits, in terms of increased trophic transmission, of multidimensionality versus unidimensionality in host manipulation remain to be established. In our study model system, the increased vulnerability to predation of G. pulex infected with P. laevis has been demonstrated, both in microcosm experiments [7,9,52], and under field conditions [8], but the traits involved in such increase have not been identified yet. Two recent studies have shown that a single altered phenotypic dimension in P. laevis infected hosts cannot explain this increased vulnerability to predation [20,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the benefits, in terms of increased trophic transmission, of multidimensionality versus unidimensionality in host manipulation remain to be established. In our study model system, the increased vulnerability to predation of G. pulex infected with P. laevis has been demonstrated, both in microcosm experiments [7,9,52], and under field conditions [8], but the traits involved in such increase have not been identified yet. Two recent studies have shown that a single altered phenotypic dimension in P. laevis infected hosts cannot explain this increased vulnerability to predation [20,52].…”
Section: Discussionmentioning
confidence: 99%
“…In our study model system, the increased vulnerability to predation of G. pulex infected with P. laevis has been demonstrated, both in microcosm experiments [7,9,52], and under field conditions [8], but the traits involved in such increase have not been identified yet. Two recent studies have shown that a single altered phenotypic dimension in P. laevis infected hosts cannot explain this increased vulnerability to predation [20,52]. Since a transient increase in serotonin appears to mimic infection syndrome in a number of dimensions (this study), we would expect its injection in G. pulex to increase its vulnerability to predation.…”
Section: Discussionmentioning
confidence: 99%
“…Although altered host colouration appears related to parasite transmission, a direct link has not been established. This caveat deserves mention because a recent study found no relationship between intermediate host appearance and predation risk in a different acanthocephalan (Kaldonski et al 2009). Here we test (1) if there is a relationship between parasite size and host colouration and (2) whether this pattern differs between male and female parasites.…”
mentioning
confidence: 96%
“…In contrast, multiplication would perform better if one poorly manipulated dimension is sufficient to decrease the overall effect on trophic transmission. Analysing the results of experiments combining predation trials with phenotypic engineering of both infected and uninfected hosts (Bakker et al, 1997;Kaldonski et al, 2009;Perrot-Minnot et al, 2012) using multiple regression techniques might provide interesting insights in this respect.…”
Section: Some Suggestions For Future Researchmentioning
confidence: 99%
“…This can be achieved through combining refined experimental design with phenotypic engineering (Kaldonski et al, 2009;PerrotMinnot et al, 2012). Furthermore, such experiments will allow one to estimate whether the effects of altered traits on enhanced transmission are additive or interactive.…”
Section: Some Suggestions For Future Researchmentioning
confidence: 99%